2018
DOI: 10.1007/s11295-018-1295-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of microsatellite loci in tree of heaven (Ailanthus altissima (Mill.) Swingle) using SSR-GBS

Abstract: Microsatellite markers are still the marker of choice for many research questions in the field of forest genetics. However, the number of available markers is often low for species that have not been studied intensively like the tree of heaven (Ailanthus altissima). During the last decade, next-generation sequencing (NGS) has offered advanced techniques for efficiently identifying microsatellite markers and accurately genotyping samples. Here, we identify new microsatellite markers for the tree of heaven by ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 46 publications
5
13
0
Order By: Relevance
“…Effective fisheries management and population persistence hinge upon understanding population structure and stock composition (Hilborn, Quinn, Schindler, & Rogers, 2003;Ruzzante et al, 2006;Schindler et al, 2010), particularly in northern species facing increased exploitation and growing pressure from climate change. Yet the paucity of genomic resources for many northern species and Our results build directly on recent studies developing panels of sequence-based microsatellites in salmonids and other taxa (Darby et al, 2016;Neophytou et al, 2018), the development of software for sequence-based microsatellite genotyping (e.g., Zhan et al, 2013) and clearly illustrates the large potential for sequence-based microsatellite genotyping to other northern fish and/or understudied species.…”
Section: Comparison Of Sequenced Microsatellites and Snpssupporting
confidence: 60%
“…Effective fisheries management and population persistence hinge upon understanding population structure and stock composition (Hilborn, Quinn, Schindler, & Rogers, 2003;Ruzzante et al, 2006;Schindler et al, 2010), particularly in northern species facing increased exploitation and growing pressure from climate change. Yet the paucity of genomic resources for many northern species and Our results build directly on recent studies developing panels of sequence-based microsatellites in salmonids and other taxa (Darby et al, 2016;Neophytou et al, 2018), the development of software for sequence-based microsatellite genotyping (e.g., Zhan et al, 2013) and clearly illustrates the large potential for sequence-based microsatellite genotyping to other northern fish and/or understudied species.…”
Section: Comparison Of Sequenced Microsatellites and Snpssupporting
confidence: 60%
“…Starting from a reasonable number of candidate loci that were identified using readily available or newly generated genomic resources, resulted in an average of 75% of the loci included in the PCR multiplex generating reliable genotypic data. This result compares favourably with previous studies where success rates were lower (47% , 53% (Neophytou et al 2018)) or similar (78% (Tibihika et al…”
Section: Workflow For Efficient Ssrseq Development In Non-model Speciessupporting
confidence: 89%
“…Previous studies have demonstrated the added benefit of analysing different types of polymorphism within sequences compared to using amplicon size only (as in traditional capillary electrophoresisbased genotyping) to differentiate alleles (Darby et al 2016;Neophytou et al 2018;Barbian et al 2018;Tibihika et al 2018). Size homoplasy, due to alleles identical by size but not by sequence, ranges from to 32% and 44% (Darby et al 2016;Vartia et al 2016;Barbian et al 2018).…”
Section: Implications Of Haplotype Based Genotypingmentioning
confidence: 99%
See 2 more Smart Citations